Gymnadenia conopsea orchid: a systematic review - Wu, Jing-Yi; Tang, Ruo-Nan; Wang, Jia-Wen; Chen, Wan-Ying; Liu, Xing; Wang, Ji-Wen; Li, Mei-Ya; Jiang, Fu-Sheng (Frontiers in Pharmacology, 2025)
BackgroundGymnadenia conopsea (L.) R. Br., a medicinally significant orchid used for millennia in China, is systematically reviewed regarding its botany, resources, ethnomedicinal applications, phytochemistry, pharmacology, and propagation strategies to advance therapeutic utilization and conservation.MethodsUsing keywords such as “G. conopsea,” “phytochemistry,” “propagation and breeding,” “bioactive compounds,” “immunomodulatory effects,” and “neuroprotective potential,” we systematically searched literature related to G. conopsea plants from databases including Web of Science, SciFinder, PubMed, ACS Publications, CNKI, Wanfang Data, Google Scholar, and Baidu Scholar.ResultsA total of 1,074 papers were retrieved and 133 full-text articles were ultimately selected and comprehensively reviewed. Up to now, over 203 metabolites have been identified in the tubers of G. conopsea, including benzyl ester glucosides, stilbenoids, phenanthrenes, phenolic derivatives, alkaloids and polysaccharides. Pharmacological studies validate its multi-target therapeutic potential across tonification, anti-fatigue interventions, oxidative stress mitigation, antiviral defense, and management of gastric ulcers and silicosis. Despite extensive research on the pharmacological properties of crude extracts, the relationship between specific bioactive compounds and their corresponding pharmacological activities, particularly in vivo, remains poorly understood. Critically, overexploitation and habitat degradation have led to its classification as an endangered species. Current propagation efforts face significant challenges, including low natural germination rates, and dependence on specific habitats and obligate mycorrhizal fungi, precluding the development of efficient large-scale cultivation and seedling production systems.ConclusionMarked progress has been made in characterizing small-molecule metabolites of G. conopsea, yet comprehensive structural elucidation of polysaccharides remains incomplete. Additionally, research must be intensified on synergistic interactions of bioactive constituents, molecular targets, mechanisms of action, and in vivo metabolic pathways to facilitate development of a quality standard system. For propagation, wild-simulated cultivation should be adopted for resource conservation, while optimizing symbiotic germination techniques is critical to overcome propagation bottlenecks, ultimately enabling sustainable utilization.